2004
DOI: 10.1002/bjs.4578
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the effects of preoperative and postoperative oral nutritional supplements on clinical course and cost of care

Abstract: Perioperative oral nutritional supplementation started before hospital admission for lower gastrointestinal tract surgery significantly diminished the degree of weight loss and incidence of minor complications, and was cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
201
3
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(218 citation statements)
references
References 74 publications
7
201
3
7
Order By: Relevance
“…This support, mainly intended to compensate for fluid loss (ASPEN Board of Directors, 1993;French Speaking Society for Parenteral and Enteral Nutrition, 1996;Italian Society of Parenteral and Enteral Nutrition, 1996), is insufficient to cover the patients' energy requirements and produces the considerable alterations described in this paper. Extensive work on perioperative multimodal management for surgical patients (Basse et al, 2002Hjort Jakobsen et al, 2004;Smedley et al, 2004) supports the important role of early, complete feeding on surgical recovery, and agrees with our results for a complete parenteral nutrition (PN4).…”
Section: Discussionsupporting
confidence: 85%
“…This support, mainly intended to compensate for fluid loss (ASPEN Board of Directors, 1993;French Speaking Society for Parenteral and Enteral Nutrition, 1996;Italian Society of Parenteral and Enteral Nutrition, 1996), is insufficient to cover the patients' energy requirements and produces the considerable alterations described in this paper. Extensive work on perioperative multimodal management for surgical patients (Basse et al, 2002Hjort Jakobsen et al, 2004;Smedley et al, 2004) supports the important role of early, complete feeding on surgical recovery, and agrees with our results for a complete parenteral nutrition (PN4).…”
Section: Discussionsupporting
confidence: 85%
“…The latter explanation is supported by an Australian survey of surgeons, which revealed a higher confidence in the surgeons' own judgment than in clinical practice guidelines and other sources of evidence (17). Almost all respondents, who gave preoperative NS, sustained the support in the postoperative period, as also suggested by many authors (18)(19)(20). It is also encouraging that almost 70% of participants prescribed oral NS products after hospital discharge to the patients who received perioperative NS.…”
Section: Discussionsupporting
confidence: 59%
“…There is evidence that early and adequate treatment of malnutrition is fundamental for improving patients' prognosis and well-being, and international evidence-based guidelines have been developed to standardise nutritional therapy (Lochs, 2006). Several clinical trials have shown that supplementation with ONS are beneficial in the perioperative setting (Beattie et al, 2000;Smedley et al, 2004). However, the impact on clinical routine still remains moderate.…”
Section: Discussionmentioning
confidence: 99%